Temporal analysis of the changes in the sand-dune barrier in the Buenos Aires Province, Argentina, and their relationship with the water resources - Carretero, Silvina (2014)
The changes in recharge possibilities of the coastal aquifer in the Partido de La Costa (Buenos Aires, Argentina) are analysed according to the changes in land use among the years 1973, 1986, 2001 and 2010. A multi-temporal analysis was carried out on Landsat satellite images, distinguishing four types of land use. The water balances were calculated and, on the basis of the infiltration values, the recharge was assessed for every situation. An important increase in urbanised areas can be observed over almost four decades. In 1973, it was difficult to distinguish architectural structures, whereas in 2010 the development of an urban grid associated with the fixation of dunes can be clearly recognised. This development is accompanied by significant population growth and an increase in water demand. The expansion of the impervious surfaces has modified the recharge conditions and the volume of the available freshwater reserves.